Lactobacillus casei Strain Shirota Enhances the Ability of Geniposide to Activate SIRT1 and Decrease Inflammation and Oxidative Stress in Septic Mice - Chao Mai; Li Qiu; Yong Zeng; Xingqin Tan (Frontiers in Physiology, 2021)
Gardenia jasminoides Ellis is rich in geniposide, which can be transformed into the anti-oxidant and anti-inflammatory agent genipin. Genipin exhibits greater efficacy than geniposide, but it is unstable and difficult to preserve. In this study, a mouse model for sepsis was established by cecal ligation and puncture, and then we explored the effects and mechanism of Lactobacillus casei strain Shirota (LcS) on the enhancement of the ability of geniposide to reduce sepsis and decrease inflammatory and oxidative levels in mice by the regulation of sirtuin type 1 (SIRT1). The mice were evaluated and analyzed by the open field test, Morris water maze test, flow cytometry, kit assay, qPCR, and western blot. The LcS + geniposide increased the survival rate in mice with sepsis, and increased the total travel distance, number of times the mice stood up, amount of time the mice spent grooming their fur, duration in the target quadrant, and crossing area number. The testing of mouse nerve cells showed that LcS + geniposide reduced the rate of nerve cell apoptosis caused by sepsis. LcS + geniposide also decreased the amount of inflammatory-related indicators of TNF-α, IL-6, and IL-1β, and the oxidation-related levels of malondialdehyde (MDA) in the hippocampi of septic mice, and it increased the oxidase activities of superoxide dismutase (SOD) and catalase (CAT). Additionally, LcS + geniposide increased the SOD1, SOD2, and CAT mRNA expression in the hippocampi of mice with sepsis and decreased the expression of TNF-α, IL-1β, NF-κB, and p53 mRNA. LcS+geniposide also increased the SIRT1 protein expression and decreased the Ac-FOXO1, Ac-NF-κB, and Ac-p53 protein expression in the hippocampi of mice with sepsis. We also observed that LcS + geniposide decreased the inflammatory and oxidative damage in the mice with sepsis. The effect of LcS + geniposide was similar to that of the drug dexamethasone and stronger than the effect of geniposide utilized alone. LcS also enhanced the ability of geniposide to activate SIRT1 and decrease the inflammation and oxidative stress in the septic mice, and it achieved an effect same with that obtained by the use of the drug dexamethasone.